A linked administrative data study examining the association between patterns of self-reported functional impairment and mortality in the ageing (65+) population in Northern Ireland. - Paul de Cock; Finola Ferry; Michael Rosato; Emma Curran; Gerard Leavey (International Journal of Population Data Science, 2018)
Background The 2011 Northern Ireland Census asked whether individuals considered themselves to have a ‘limiting long-term health problem or disability’. This question was followed by 11 questions as to the nature of the long-term (12+ months) functional impairment(s) people are experiencing (problems with: hearing, sight, communication, mobility, learning difficulties, mental health, pain, breathing, memory, chronic conditions or other conditions).